Non-invasive prenatal testing: a revolutionary journey in prenatal testing - Abedalthagafi, Malak; Bawazeer, Shahad; Fawaz, Romy I.; Heritage, A. Merrihew; Alajaji, Nouf M.; Faqeih, Eissa (Frontiers in Medicine, 2023)
The detection of cell-free fetal DNA (cff-DNA) in maternal plasma was first reported in 1997. This discovery paved the way for the development of a new field in pre-natal diagnosis. Based on the discovery, noninvasive prenatal testing (NIPT) is now being used by millions of pregnant women annually.This review highlights the important genetic conditions where basic scientific discoveries can be translated and applied in the clinic for improved diagnosis. It also touches upon the ethical questions on the implications of expansion of this technology where the disease conditions, or its impact on the developing fetus are not completely understood.